Implementing web customization of 3D interior home design - Yoon, Elvis Yu Jing (Universiti Malaysia Sarawak (UNIMAS), 2015)
It is common nowadays for consumers to customize their products according to their preferences before purchasing. However, home customization is currently rarely adopted in Malaysia. Custom homes are known as unique houses that are built for specific customers according to their own preferences. These specially built houses allow users to have control over the layout and design of their house so that each and every unit of the house will be different depending on the client‟s wants and needs. This is to ensure that the user‟s needs are fulfilled and they will be satisfied with their future house. All this would increase customer satisfaction and improve usability of the new house. Therefore, this project endeavors to implement a website where people can easily customize the internal layout and design of their house using a web application. To implement this system, Unity3D is used to create the application. Upon completion, the system will be evaluated for its usability through qualitative study.